To Temper or Not to Temper: A Petrographic Textural Study of Clays and Formative Ceramic Sherds from the Valley of Oaxaca, Mexico - (:unkn) unknown (My University, 2016)
Ceramics are one of the best forms of material culture archaeologists can use to analyze questions of social, political, economic, and ideological complexity. The purpose of this thesis research is to determine if the clays used to manufacture later Middle Formative-Terminal Formative ceramics in the Valley of Oaxaca were tempered or otherwise modified by looking at texture of sherds petrographically. Clay samples from around the valley, modern sherds, and Formative sherds were examined and compared using six different forms of analysis. The results show that it is most probable that the Formative sherds were not tempered. However, several sherds exhibited unusual texture that could be considered suspect for tempering. This research provides an approach to textural analysis that is helpful in the comparison of results from other forms of compositional analysis.
Keywords: Ceramics; Clays; Formative Mesoamerica; Petrography; Valley of Oaxaca